Hubungan Antara Terapi Wudhu Sebelum Tidur dengan Kualitas Tidur pada Mahasiswa - Astry Ratna Afriyanti; Wigyo Susanto; Dwi Heppy Rochmawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
Sleep disturbances can result in physical problems and a decrease in a person's ability to focus. Ablution can serve as a way for relaxation that helps improve sleep quality. This study aims to explore the relationship between ablution performed before bed and sleep quality among students. This type of research is pre-experimental. The data used in this study was collected through a questionnaire given directly to the respondents. A total of 50 respondents were involved as a sample in this study. The sampling method used is total sampling. To analyze the data, univariate and bivariate tests are used, where bivariate analysis is carried out by chi-square test. The results of the univariate analysis showed that 78% of respondents always performed ablution, while 22% only did it occasionally. Good sleep quality was found in 68% of respondents, while 32% experienced poor sleep quality. Most respondents were 20 years old, reaching 42%, with the lowest being 19 years old at 10%. In terms of gender, 68% of respondents were male and 32% were female. Bivariate analysis using the Chi-Square test showed that there was no significant relationship between the practice of ablution before bed and the quality of students' sleep, with a value of 0.591 which was greater than 0.005. Therefore, it can be concluded that there is no relationship between the practice of ablution before bed and the quality of sleep among students.